Depletion of Cytotoxic T-Cells Does Not Protect NUP98-HOXD13 Mice from Myelodysplastic Syndrome but Reveals a Modest Tumor Immunosurveillance Effect - Gough, Sheryl M. (Public Library of Science, 2012)
Myelodysplastic syndrome (MDS) and aplastic anemia (AA) patients both present with symptoms of bone marrow failure. In many AA patients, these features are thought to result from an oligoclonal expansion of cytotoxic T-cells that destroy haematopoietic stem or progenitor cells. This notion is supported by the observation that AA patients respond to immunosuppressive therapy. A fraction of MDS patients also respond well to immunosuppressive therapy suggesting a similar role for cytotoxic T-cells in the etiology of MDS, however the role of cytotoxic T-cells in MDS remains unclear. Mice that express a NUP98-HOXD13 (NHD13) transgene develop a MDS that closely mimics the human condition in terms of dysplasia, ineffective hematopoiesis, and transformation to acute myeloid leukemia (AML). We followed a cohort of NHD13 mice lacking the Rag1 protein (NHD13/Rag1KO) to determine if the absence of lymphocytes might 1) delay the onset and/or diminish the severity of the MDS, or 2) effect malignant transformation and survival of the NHD13 mice. No difference was seen in the onset or severity of MDS between the NHD13 and NHD13/Rag1KO mice. However, NHD13/Rag1KO mice had decreased survival and showed a trend toward increased incidence of transformation to AML compared to the NHD13 mice, suggesting protection from AML transformation by a modest immuno-surveillance effect. In the absence of functional Tcrb signaling in the NHD13/Rag1KO T-cell tumors, Pak7 was identified as a potential Tcrb surrogate survival signal.